Specnuezhenide suppresses diabetes-induced bone loss by inhibiting RANKL-induced osteoclastogenesis - Ye Xiaoshuang; Jiang Juanjuan; Yang Juan; Yan Wenyan; Jiang Luyue; Chen Yan (Acta Biochimica et Biophysica Sinica, 2022)
Diabetes osteoporosis is a chronic complication of diabetes mellitus (DM) and is associated with osteoclast formation and enhanced bone resorption. Specnuezhenide (SPN) is an active compound with anti-inflammatory and immunomodulatory properties. However, the roles of SPN in diabetic osteoporosis remain unknown. In this study, primary bone marrow macrophages (BMMs) were pretreated with SPN and were stimulated with receptor activator of nuclear factor kappa B ligand (RANKL; 50 ng/mL) to induce osteoclastogenesis. The number of osteoclasts was detected by tartrate-resistant acid phosphatase (TRAP) staining. The protein levels of cellular oncogene fos/nuclear factor of activated T cells c1 (c-Fos/NFATc1), nuclear factor kappa-B (NF-κB), and mitogen-activated protein kinases (MAPKs) were evaluated by western blot analysis. NF-κB luciferase assays were used to examine the role of SPN in NF-κB activation. The DM model group received a high-glucose, high-fat diet and was then intraperitoneally injected with streptozotocin (STZ). Micro-CT scanning, serum biochemical analysis, histological analysis were used to assess bone loss. We found that SPN suppressed RANKL-induced osteoclast formation and that SPN inhibited the expression of osteoclast-related genes and c-Fos/NFATc1. SPN inhibited RANKL-induced activation of NF-κB and MAPKs. In vivo experiments revealed that SPN suppressed diabetes-induced bone loss and the number of osteoclasts. Furthermore, SPN decreased the levels of bone turnover markers and increased the levels of runt-related transcription factor 2 (RUNX2), osteoprotegerin (OPG), calcium (Ca) and phosphorus (P). SPN also regulated diabetes-related markers. This study suggests that SPN suppresses diabetes-induced bone loss by inhibiting RANKL-induced osteoclastogenesis, and provides an experimental basis for the treatment of diabetic osteoporosis.